Environmental performance assessment of the application of high temperature phase change materials in waste-to-energy plants. (December 2017) - Mengarelli, Marco; Magro, Fabio dal; Py, Xavier; Romagnoli, Alessandro
Abstract: The constantly growing worldwide population is leading to a constant increment of waste production. In most developing and developed countries an ongoing key challenge is to collect, recycle, treat and dispose consistent quantities of solid waste. In this context, Waste-to-Energy (WtE) plants play a crucial role as they convert waste into energy. Among the different technical issues, temperature fluctuations of the flue gas and high temperature corrosion represent two of the main limitations to the plant efficiency. A possible solution consists of using a refractory brick containing a Phase Change Material (PCM) to enable the installation of additional superheaters in the combustion chamber in order to increase the temperature of the superheated steam without provoking corrosion, which allows the overall electrical efficiency to be increased. This study assesses the environmental impact originated by the employment of the aforementioned technology by means of Life Cycle Assessment (LCA). In particular, an LCA comparison study between a "standard" WtE plant configuration and a PCM-equipped plant is carried out. The comparison aims to highlight the environmental burdens generated by the employment of an additional quantity of refractory material, as well as the adoption of PCM and the modifications applied at system level (e.g. heat exchanger surfaces). On the contrary, such negative contribution should be mitigated by the increment in the electric efficiency of the plant which, given a definite amount of solid waste input to handle would return a higher amount of electric energy as output.